Violence and Absence - Willett, Mischa (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
In several poems, Wordsworth considers the active representation of absence-- a stone circle, a zero, an “O the difference to me!”-- as a response to violence. Absent histories create our own involuntary misreadings, well-rehearsed in New Historicist debates surrounding Tintern Abbey, and Three Years She Grew, but present absences can heighten the descriptive violence as in a Hitchcock film where one only hears the scream as a camera cuts away, or as in Wordsworth’s lesser-known Alice Fell, wherein the violence reeked upon a girl is displaced onto surrounding objects making it at once more palatable and more subversive. This paper’s method is to consider Ovid, Wordsworth’s favorite poet as a young man, as a likely template for this trope. I show that certain of Wordsworth’s poems emerged as exercises in Ovidian imitation, and that he used the erasure of this poetic father to add darkness and suggestion to poems that are often misread as innocent.